Etno-história Guarani e a construção do espaço a partir da arquitetura: um estudo de caso na Aldeia Tekoha Añetete. - Kühl, Gracieli Erna Schubert (2013)
This dissertation is characterized as a case study in Guarani Indian village named the Tekoha Añetete reservation, Village in the municipality of Diamante d'oeste\/PR. Aims to register main cultural aspects of group through reports on the construction of the living space and the architecture itself. The problem of this activity is devoted to the traditional architecture of the Guarani as opposed to architecture developed by external agents inside the village, among them the Cohapar (housing Company of Paraná) and Itaipu Binacional. Among these buildings are residences and prays. The discussion is divided into three chapters. Initially presents concepts related to the problem, among them: culture, identity, territory. In a second moment is made a dense description of the village in order to characterize it as an object of study. In the third chapter are addressed the architectural works present in the village, including the traditional architecture of the Guarani, the architecture introduced by the Cohapar and the works made by Itaipu, besides brief analysis on merger of these works made by external agents to the sociocultural dynamics of the group from the anthropological gaze of Rubem Thomaz de Almeida.